MODEL KOMUNIKASI DALAM FILM ADIT SOPO JARWO EPISODE: BERSAHABAT AGAR KITA HEBAT - Meilita Teza Warman Warman; Oktri Permata Lani (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2025)
The aim of this research is to identify various forms of communication that occur in the film